Effect of stiffness on the seismic performance of code-conforming reinforced concrete shear wall buildings. (15th September 2020) - Cando, M.A.; Hube, M.A.; Parra, P.F.; Arteta, C.A.
Highlights: Performance of shear wall buildings was improved by increasing the lateral stiffness. Larger stiffness reduced the probability of exceeding life safety limit state. Larger stiffness reduced the probability of collapse for the same IM. Larger stiffness increased the probability of collapse in 50 years. Displacement ductility increased when the stiffness of the building decreased. Abstract: This study assesses the effect of the stiffness on the seismic performance of residential shear wall buildings designed according to current Chilean regulations, including DS60 and DS61. Specifically, the paper focuses on the effect of stiffness on the building overstrength, displacement ductility, fragility for Life Safety (LS) and collapse limit states, as well as the probability of achieving these two limits states in 50 years. The seismic performance is assessed for a group of four 20-story residential shear wall buildings archetypes located in Santiago. Walls were modeled using the multiple vertical line element model (MVLEM) with inelastic hysteretic materials for the vertical elements, and a linear-elastic shear behavior. Pushover analyses were considered to estimate the buildings overstrength and displacement ductility, while incremental dynamic analyses were performed to estimate fragility curves. A probabilistic seismic hazard analysis, which considered the seismicity of Chile central zone, was performed to estimate the probability of achieving the two limits states in 50 years. The results show that an increase in the stiffness reduces the chance of exceeding the LS and collapse limit states for the same intensity level. Additionally, the probabilistic seismic hazard analysis shows that, when the stiffness increases, the probability of reaching the LS limit state in 50 years also decreases. Counterintuitively, the probability of collapse in 50 years increases as the stiffness increases, due to the considered seismic hazard and the design requirements. Since society is moving towards resilient structural designs that minimize damage, disruption and economic losses, it is concluded that the performance of reinforced concrete shear wall buildings is improved by increasing the stiffness.